2021
DOI: 10.21931/rb/2021.06.04.18
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and molecular evolutionary analysis of SENV DNA isolated from Iraqi Hepatitis Patients

Abstract: SEN Virus (SENV) is a newly discovered group of transmissible, hepatotropic, single-stranded, circular, non-enveloped DNA viruses that are distantly linked to the widely distributed Torque Teno Virus (TTV) family. This research aimed to use nucleotide sequencing to identify the genetic alterations of SEN-V and to investigate the similarities between isolates. Seven DNA samples of SENV, which were previously extracted from blood of post transfusion hepatitis, were used to identify the genetic variation of SEN-V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 13 publications
3
1
1
Order By: Relevance
“…And these findings are disagreed with Takemoto et al ( 2015) who showed that the majority of dialysis patients were males (55%) with a mean age of 53.8 years (42) . In addition, there is no significant statistical association between TTV and clinical characteristics or risk factors according to the table (3). These results are in agreement with Akbari et al ( 2018) who observed that there is no significant relation between TTV infection and hypertension (43) .…”
Section: Phylogenetic Treesupporting
confidence: 88%
See 4 more Smart Citations
“…And these findings are disagreed with Takemoto et al ( 2015) who showed that the majority of dialysis patients were males (55%) with a mean age of 53.8 years (42) . In addition, there is no significant statistical association between TTV and clinical characteristics or risk factors according to the table (3). These results are in agreement with Akbari et al ( 2018) who observed that there is no significant relation between TTV infection and hypertension (43) .…”
Section: Phylogenetic Treesupporting
confidence: 88%
“…On the other hand, disagree with Hassuna et al who showed that there is a correlation between TTV viremia and age (40) . Regarding sex of studied patients, the higher rate (88.1%) of TTV DNA infection was in female rather than male (75.9%) with no significant association between sex and TTV DNA-status, as shown in table (3). These results are in accordance with Mohamed et al (2017) who showed that the percentage of patients who were positive for TTV as (66.7%), out of Iraqi JMS 2022; Vol.…”
Section: Phylogenetic Treesupporting
confidence: 86%
See 3 more Smart Citations